Point of Zero Charge Determination and the Inluence of P, Basic Slag, Organic Matter and Lime Applications on Colloidal Charge and Quality of Oxisols - MARKUS ANDA; ANTONIUS KASNO; WIWIK HARTATIK; . SULAEMAN; J. SRI ADININGSIH (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2001)
The colloidal charge manipulation of highly weathered soils using point of zero charge (PZC or pHo) approach is important in improving soil chemical properties. The objective of this study was to determine the PZC and manipulate colloidal charge surfaces of Oxisols in order to increase their quality. PZC was determined by adjusting pH values from 3 to 7 using potentiometric titration. The change of colloidal surface charges was measured using two extractants; NH4-acetat pH 7 and NH4Cl. A glass house experiment was carried out using 4.5 kg soil/pot. Soil was taken from Sonay, South East Sulawesi and from Sitiung, West Sumatra. Soil was taken from surface layer (0-20 cm) and subsurface layer (20-40 cm) for each location. Four factors consisted of P fertilizer, basic slag, organic matter and lime were used to manipulate colloidal surface charge. The treatment rates were 100, 200 and 400 ppm P for P fertilizer; 2, 4 and 8 t/ha for basic slag; 10, 20 and 40 t/ha for organic matter; 1.5, 3 and 6 t/ha for lime, and a complete control. All 13 treatments with three replications, were arranged using a randomized complete block design in which each layer of two Oxisols is used as a block. The results showed that values of PZC for a surface layer of Sonay Oxisol (OSY) and for surface and subsurface layers of Sitiung Oxisol (OSG) are similar, i.e, pHo was 3.5. In addition, the PZC value for the subsurface layer of OSY occurs at pH 5 which is the highest pHo value compared to three other layers. The PZC value of OSY, at a surface layer is higher than its soil pH value (5.0 vs 4.4) suggesting that colloidal surfaces bear a positive charge. In contrast, the PZC values for the surface layer of OSY and surface and subsurface layers of OSG were lower than their soil pH values, indicating the colloidal surfaces bear a negative charge. Application of P, basic slag, organic matter, and lime was able to manipulate colloidal charge surfaces having positive charges become negative and that the low negative charge of colloidal surfaces become more negative as evidenced from the increase cation exchange capacity (measured in NH4Cl) compared to a control treatment. Application of P, basic slag,organic matter, and lime could increased quality of Oxisols as shown by decreasing K leaching and by increased soybean yields, which drastically increased compared to a control treatment.